Real-time simulation and performance of DSTATCOM using an improved load current detection-based control technique for compensation of current harmonics and load transients. Issue 1 (2nd January 2021) - Penthia, Trilochan; Panda, Anup Kumar; Mangaraj, Mrutyunjaya
ABSTRACT: Current harmonics are introduced in a distribution system due to the increasing utilization of nonlinear loads. Therefore, elimination of harmonics from supply current is an inevitable task to do. In this paper, an adaptive control technique called I-cos-theta (Icosθ) control algorithm along with a Kernel-based training method is proposed in a fuel cell-based Distributed STATic COMpensator (DSTATCOM) simulation for harmonic compensation. Specifically, the direct and quadrature components of the load current are extracted and retrained using the Kernel-based Icosθ control algorithm. The control algorithm is implemented to generate reference currents, and then the appropriate switching pulses for the Voltage Source Inverter (VSI) of the DSTATCOM. The fuel cell is intended to maintain the DC-link voltage of the DSTATCOM during different loading conditions for power quality improvement. Further, the DC-link voltage is maintained constant at 530 V with an acceptable voltage regulation of <±16%, even under load transients and temporary supply failure conditions. Moreover, the simulation of the fuel cell-based DSTATCOM has been performed in Sim Power System (SPS)/MATLAB Simulink software. Also, a low power rated prototype is developed to verify the proposed simulation model, incorporating with the dSPACE1104 real-time environment.